Hepatogenic weakness as a clinical marker of hyperammonemia and of the effectiveness of its correction in patients with pre-cirrhotic stages of non-alcoholic fatty liver disease - E. M. Petrova; V. A. Cheraneva; V. G. Grachev (Лечащий Врач, 2021)
The aim of this work was identification of markers of of hyperammonemia (HA) available in routine practice, and assessment of the effectiveness of ornithine in treatment of HA and its clinical manifestations in patients with NAFLD at the pre-cirrhotic stage.Outpatients with NAFLD with hepatic steatosis were assessed for liver tests, fibrosis on the FIB-4 scale, hepatogenic weakness on the visual analogue scale, and the blood ammonia level, correlations between these indicators are determined. After a 4-week course of ornithine 15 g/day orally, the dynamic of ammonia and hepatogenic weakness was assessed in some patients.41 patients were included, mean age 46 ± 10 years. The mean hepatogenic weakness was 5.36 ± 1.38 points with a score of 5 points or higher in 70% of patients. The average blood ammonia level was 108 ± 53.3 μmol/l. HA with an ammonia level > 60 μmol/l was observed in 36 patients (87.8%). Correlation analysis revealed a significant direct relationship between the level of ammonia and GGTP (ρ = 0.418, p = 0.017), as well as between ammonia and hepatogenic weakness (ρ = 0.358, p = 0.047). Ornithine therapy in 17 patients was accompanied by a significant decrease in ammonemia (from 141.5 ± 54.9 to 98.5 ± 47.2 μmol/l, p = 0.0001) and hepatogenic weakness (from 5.64 ± 1.39 to 4, 14 ± 1.70 points, p = 0.014).It was found that patients with early stages of NAFLD have a high prevalence of HA. The degree of hepatogenic weakness and the level of GGTP reflect the severity and can be used as markers of this disorder. Ornithine can effectively reduce the level of ammonia and improve clinical symptoms in patients with NAFLD.